The biotechnology of effluent-grown Spirulina, and application in aquaculture nutrition - Maart, Brenton Ashley (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1993)
The biotechnology of production and utilisation of the cyanobacterium Spirulina has been well documented. Research has centred mainly on application in human and animal nutrition, and has been motivated by the high protein, vitamin, fatty acid and growth factor contents. The main obstacle in realising the full potential of this feed source has been the high production costs associated with its mass culture in defined media. The observation of blooms of Spirulina in tannery effluent evaporation ponds in Wellington, South Africa, prompted this investigation into the harvesting, and nutritional and toxicological evaluation of this potentially low-cost production system, with the ultimate aim of using the product in aquaculture rations. An investigation of the chemical gradient along the evaporation cascade showed a positive correlation between the prevailing chemical conditions and the dominant species populations. A standing crop of 9.5 tonnes/ha of Spirulina was found to be present in the latter alkaline ponds, characterised by relatively lower organic and sulphur contents. Initial harvesting of the biomass was achieved by the design, construction and implementation of a small-scale screen harvest, which yielded a 25 kg (dry weight) crop. A scale-up model was then designed, and implemented in a technical scale harvest, yielding a crop of 250 kg (dry weight). Both these harvests utilised the bloom of surface-autoflocculated biomass. Concentrated cell slurries were sun-dried on muslin beds, and milled to a coarse powder. An evaluation of the harvest revealed a chemical content similar to other published reports of defined media cultures, with the exception of the protein and amino acid contents. The observed lower levels of the latter two are almost certainly due to the sun-drying method employed, known to reduce the protein content due to thermal denaturation. Legislation demands the strict toxicological evaluation of new protein sources, and because of the effluent-nature of the growth medium of this source of Spirulina, its viability lies only in the application as an animal feed or supplement. A range of toxicological tests were chosen that were targeted to elucidate the possible toxicological constraints of this effluentgrown source of protein in animal nutrition. The nucleic acid and pesticide contents of the harvested biomass were within the prescribed safety ranges. Atomic absorption showed minimal accumulation of minerals and heavy metals from the effluent. A bioassay with the brine shrimp Anemia salina showed that the biomass contained no toxicologically active water-soluble components. A short term feeding trial with new-born chicks showed that supplementation with Spirulina had no effect on the growth rates and feed conversion ratios of the different feeding groups. Pathological analyses showed that the liver was the only target organ to elicit a change in response to supplementation of the diets with Spirulina. A general decrease in liver weight was noted, with Cu, Ca, Fe and Zn being significantly accumulated. A histopathological examination however, showed no cellular and functional aberration from the control animals. The toxicological analyses gave the preliminary safe go-ahead for the evaluation of effluent-grown Spirulina in aquaculture nutrition. The South African abalone Haliotis midae, and the rainbow trout Oncorhynchus mykiss were chosen as representative species of edible cultured organisms. The technology for the culture of the perlemoen abalone is being established in South Africa, with the main area of research being the development of an artificial diet for high density culture. A 40 day growth trial demonstrated that lower concentrations of Spirulina supplemented to an agar-based fishmeal diet resulted in growth rates and feed conversion ratios similar to the control fishmeal and purified-casein diets, and thus has application potential in the nutrition of this high-cost marine delicacy. The aquaculture technology of freshwater rainbow trout is already well established. An eight week feeding trial with various concentrations of Spirulina showed that this effluent-grown protein source can partially replace fishmeal in semi-purified diets. Fish fed Spirulina did not exhibit decisive manifestations of toxicity, as determined in a histopathological study. In addition, Spirulina supplementation resulted in enhanced colouration of the skin and flesh, which may have implications in the aesthetic marketing of this sought-after table fish. The primary aim of this preliminary investigation thus concerned the determination of the biotechnological potential of this effluent-source of Spirulina. A technology transfer from the economically unfeasible defined-media culture was implemented. This project is ultimately aimed as a contribution towards the treatment of tannery wastewater, by the removal of contaminants from the effluent in the form of organic biomass.
Keywords: Aquaculture; Spirulina; Algae -- Biotechnology; Fishes -- Feeding and feeds